Properties Of Bioactive Glass Reinforced Polyurethane Scaffold By Solvent Casting/Particulate Leaching Method - Suhaimin, Intan Syazana (2019)
The properties of polyurethane-Bioglass® (PU-BG) scaffolds have been optimized using solvent casting/particulate leaching (SC/PL) method. Processing parameters such as polymer solution concentration (15, 16, 17, 18 and 19 wt/vol%), leaching agent concentration with ratio between PU and NaCl (1:3, 1:4, 1:5, 1:6 and 1:7), leaching agent composition by percentage of NaCl/NaHCO3 (100/0, 85/15, 75/25, 65/35, 55/45 and 45/55) and percentage of Bioglass® (0, 10, 20, 30 40 and 50 wt%) were investigated to obtain the desired properties of PU-BG scaffolds. The scaffolds were characterized using field emission scanning electron microscopic (FESEM), porosity test, fourier transform infrared (FTIR), compression test, inductively coupled plasma (ICP) and degradation test. The optimum parameters to fabricate PU-BG scaffold were found to be 19 wt/vol % of polymer solution concentration, 1:6 ratio (PU: NaCl) of leaching agent concentration and leaching agent composition between 65% NaCl and 35% NaHCO3. The optimization process was able to fabricate the composite scaffold with the thickness more than 20 mm without the formation of undesirable dense layer. Besides, the PU-BG scaffolds were observed with well interconnected porous structure with the pore size spanning over a wide range and adequate porosity for the bone tissue application. The results demonstrated that, the increased in percentage of Bioglass® from 0 wt% to 50 wt% was found to improve the compressive strength as well as induced and accelerated an apatite formation during in-vitro test.